2009
DOI: 10.1159/000222090
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Cerebral Gliomas in Northwest Greece and Study of Potential Predisposing Factors, 2005–2007

Abstract: Background: To investigate the epidemiologic and clinical characteristics (age, sex, tumor location, socioeconomic status) and potential predisposing factors (alcohol, tobacco, mobile phone use, severe head trauma) of cerebral gliomas in a defined area of Northwest Greece. Methods: The prospective study was conducted in patients with gliomas referred to all 7 hospitals of a study area with a population of 488,435 inhabitants, from June 1, 2005, to May 31, 2007. Incidence rates (IR) were calculated as new cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 62 publications
1
47
0
4
Order By: Relevance
“…These differences could be attributed to racial, genetic, and environmental factors, which may influence the development of primary brain tumors [4]. For example, cerebral glioma appears to be more common in the Caucasian population than in Japan, Hispanic-Americans, and African Americans [15,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…These differences could be attributed to racial, genetic, and environmental factors, which may influence the development of primary brain tumors [4]. For example, cerebral glioma appears to be more common in the Caucasian population than in Japan, Hispanic-Americans, and African Americans [15,28,29,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] The estimated odds ratios from the largest case-control study including 416 cases were not consistent with an association. 13 Of the other casecontrol studies, most of which included less than 150 cases, two reported an increased risk of glioma associated with increased consumption of wine 8 and increased consumption of beer, liquor and total alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Those that have, have reported inconsistent results. [8][9][10][11][12][13][14][15][16][17] Some of these studies were small, did not distinguish glioma from meningioma, and were affected by cases' poor recall of alcohol consumption due to cognitive impairment from rapidly progressing tumors and side-effects of treatment. …”
mentioning
confidence: 99%
“…The average annual age-adjusted IR of GBM is variable, ranging from 0.59 per 100,000 persons to 3.69 per 100,000 persons (11,(13)(14)(15)(16)(17), and is the highest among malignant primary brain tumors (Table 1).…”
Section: Incidence Of Glioblastomamentioning
confidence: 99%